The competency-based training model for vocational high school teachers from electrical expertise programs - Malik, Muhammad Nasir; Soenarto, S.; Sudarsono, FX. (Jurnal Pendidikan Vokasi, 2018)
The study was to generate a valid, practical and effective competence-based training model for the electricity program vocational high school teachers. The type of the study was research and development that referred to the development stages proposed by Plomp. The data gathering instrument for the study consisted of: (1) validation sheet; (2) observation sheet; and (3) response questionnaire for the training participants and the trainers. In order to measure the level of reliability and the level of agreement consistency among the raters, the researcher implemented the Cohen's Kappa coefficient statistics has a minimum value of â‰¥ 0.70. The subjects of the study were the electricity program vocational high school teachers in the City of Makassar and the Regency of Gowa totaling 22 people. The results of the study were as follows: (1) the training model had fulfilled the criteria of validity so that the model might be implemented for the training activities of electricity program vocational high school teachers; (2) the training model had fulfilled the criteria of practicality that were measured from the level of model stage (syntax) implementation; (3) the training model had fulfilled the criteria of effectiveness that had the following indicators: (a) the level of knowledge and understanding exposed by the training participants, (b) the level of teaching skills exposed by the training participants, (c) the quality of training participants' portfolio and (d) the response of the training participants and the trainers.